The con and the FBI agent: an unlikely alliance - Nadolski, David (Rowman & Littlefield, 2022)
Bad Choices, Bad Days -- Like Father, Like Son -- The FBI Academy -- Life on the Inside -- Doing My Own Time -- Tunnel Vision -- The Promised Land -- The Library Card -- Paths Converge -- Heartbreak in Cambridge -- Parole -- Undercover and Underdressed -- Stuff is Getting Real -- Getting Wired -- Best Pancakes in Town -- "Stealing" a Van -- The Dry Run -- A Wolf in Sheep's Clothing -- Tony's New Digs -- Team Huddle -- Will She Stay or Will She Go? -- Finding a Steady Rhythm -- On Edge -- Hammer Time.